Atomic force microscopic analysis of the binding of the Schizosaccharomyces pombe origin recognition complex and the spOrc4 protein with origin DNA - Gaczynska, Maria (National Academy of Sciences, 2004)
In eukaryotes, the initiation of DNA replication requires the interaction between origin sequences and the origin recognition complex (ORC), which is highly conserved. In this report, atomic force microscopy (AFM) was used to examine the binding of Schizosaccharomyces pombe (sp) ORC and the spOrc4 protein with the sp autonomously replicating sequence 1 (ars1). AFM imaging revealed that spORC binding to ars1 occurred solely through spOrc4p and depended on the N-terminal AT-hook domains present in spOrc4p. At high molar ratios of spORC (or spOrc4p alone) to DNA (6:1), all of the input ars1 was bound in a one protein complex to one plasmid manner. Restriction digestion and AFM analysis of protein–DNA fragments revealed the presence of two binding sites in ars1. One site mapped to a region centered at nucleotide 838 of ars1 previously detected by DNase I protection that was reported to be essential for the autonomously replicating sequence activity of ars1. The second site mapped to a previously uncharacterized region centered at nucleotide 1148. AFM showed that the length of the DNA fragment complexed with either spORC or spOrc4p was shortened by ≈140 bp, suggesting the wrapping of two turns of the DNA around the spOrc4p alone as well as the spOrc4p in spORC. We also show that treatment of the spORC (spOrc4p)–ars1 complex with topoisomerase I induced a negative shift in the topoisomer distribution. These findings suggest that the binding of spORC to origin DNA alters the structure of the DNA. Thus, in the case of spORC, due to its unusual spOrc4p, at least two factors are likely to influence ars1 activation. These include the selective binding of the complex to A- and T-rich regions and the alteration of the DNA structure due to its wrapping around spOrc4p.